The Impact of Contemporary Children’s Literature (CCL) in enhancing English proficiency: teachers’ perspectives - Ainul Aishah Awang; Azlina Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 2024)
The integration of Contemporary Children’s Literature (CCL) is a promising avenue for elevating English proficiency among upper primary students. Therefore, this study aimed to investigate primary school teachers’ perceptions of the impact of CCL in ESL classrooms. A mixed-method research approach that adopted a case study was employed in this study. The respondents were 72 primary school English teachers from Year 4 to Year 6 teaching in urban schools in Tawau district in Sabah, Malaysia, who were selected using purposive sampling, while interviewees were selected using convenience sampling. Data were collected using a survey questionnaire, and semi-structured interviews were conducted with seven volunteer teachers. Descriptive statistics (frequency and percentage) were used to analyze the quantitative data, and thematic analysis via Atlas.ti was used for qualitative data. The findings revealed that the majority of respondents perceived the effectiveness of using CCL in enhancing English proficiency. The impact of CCL can be observed on student engagement, alignment with curriculum goals, enhancement of multiple language skills, and overall impact of CCL on teaching and learning. This study underscores the potential of CCL to advance ESL education and contributes to actionable insights into the evolution of the English curriculum in Malaysia.